The post 1990 Brazilian trade liberalization and the performance of large manufacturing firms: Productivity, market share and profits - Donald A. Hay (Institute for Applied Economic Research (ipea), 2015)
This paper analyses the effects of the 1990 Brazilian trade liberalization on the total factor productivity, market share and profits of a sample of 349 large manufacturing firms. A panel data production function analysis for the period 1986/94 indicates very large total factor productivity gains in the period to 1994, which were accompanied by large falls in market shares and profits. The explanation advanced is that the shock of trade liberalization to profits was so great that firms were stimulated to improve their efficiency dramatically.
Keywords: 330